Absence of the β1 subunit of AMP‐activated protein kinase reduces myofibroblast infiltration of the kidneys in early diabetes. Issue 2 (26th April 2019) - Choy, Suet‐Wan; Fraser, Scott A.; Katerelos, Marina; Galic, Sandra; Kemp, Bruce E.; Mount, Peter F.; Power, David A.
Summary: Activation of the heterotrimeric energy‐sensing kinase AMP‐activated protein kinase (AMPK) has been reported to improve experimental diabetic kidney disease. We examined the effect of type 1 diabetes in wild‐type (WT) mice and mice lacking the β1 subunit of AMPK (AMPK β1 −/− mice), which have reduced AMPK activity in kidneys and other organs. Diabetes was induced using streptozotocin (STZ) and the animals followed up for 4 weeks. Hyperglycaemia was more severe in diabetic AMPK β1 −/− mice, despite the absence of any difference in serum levels of insulin, adiponectin and leptin. There was no change in AMPK activity in the kidneys of diabetic WT mice by AMPK activity assay, or phosphorylation of either the αT172 activation site on the α catalytic subunit of AMPK or the AMPK‐specific phosphosite S79 on acetyl CoA carboxylase 1 (ACC1). Phosphorylation of the inhibitory αS485 site on the α subunit of AMPK was significantly increased in the WT diabetic mice compared to non‐diabetic controls. Despite increased plasma glucose levels in the diabetic AMPK β1 −/− mice, there were fewer myofibroblasts in the kidneys compared to diabetic WT mice, as evidenced by reduced α‐smooth muscle actin (α‐SMA) protein by Western blot, mRNA by qRT‐PCR and fewer α‐SMA‐positive cells by immunohistochemical staining. Albuminuria was also reduced in the AMPK β1 −/− mice. In contrast to previous studies, therefore, myofibroblasts were reduced in the kidneys of AMPK β1 −/− diabetic mice compared to diabetic WT mice, despite increased circulating glucose, suggesting that AMPK can worsen renal fibrosis in type 1 diabetes.